2008
DOI: 10.1021/ja803899q
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of the Conditions for Breathing of Metal Organic Framework Materials Using a Combination of X-ray Powder Diffraction, Microcalorimetry, and Molecular Simulation

Abstract: The adsorption of C1 to C4 linear hydrocarbons in the flexible metal organic framework MIL-53(Cr) has been followed by adsorption manometry coupled with microcalorimetry and Synchrotron X-ray powder diffraction. This experimental investigation was completed by molecular modeling. In the case of methane, the solid remains rigid whatever the adsorbate amount. However for the C2-C4 series, an increasing flexibility of the structure is observed, which is ascribed first to a breathing of the material from a large p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
271
4
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(297 citation statements)
references
References 38 publications
21
271
4
1
Order By: Relevance
“…1 The MIL-53 materials family, 2 a particularly eye-catching case of the last category, has attracted a lot of attention due to its large flexibility and the occurrence of a double structural transition upon adsorption of some gases (CO 2 , H 2 O, C 2 H 6 ,...) but not others (H 2 , CH 4 ). 3 It was also reported very recently 4 that liquid phase adsorption of para-xylene does induce a structural transition, while ortho-and meta-xylene do not. The studies performed so far, both experimentally and by molecular simulation, mainly focused on structural characterization and energetics (by calorimetry, forcefield-based calculations and DFT).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…1 The MIL-53 materials family, 2 a particularly eye-catching case of the last category, has attracted a lot of attention due to its large flexibility and the occurrence of a double structural transition upon adsorption of some gases (CO 2 , H 2 O, C 2 H 6 ,...) but not others (H 2 , CH 4 ). 3 It was also reported very recently 4 that liquid phase adsorption of para-xylene does induce a structural transition, while ortho-and meta-xylene do not. The studies performed so far, both experimentally and by molecular simulation, mainly focused on structural characterization and energetics (by calorimetry, forcefield-based calculations and DFT).…”
mentioning
confidence: 75%
“…8 We now turn to the issue of how the presence or absence of guest-induced structural transitions can be related to the properties of the guest molecule. New experimental data on the adsorption of various species in the pores of MIL-53 have been published very recently, in both gas phase (for C n H 2n+2 , n e 4) 3 and liquid phase (for o-, m-, and p-xylene). 4 In the case of materials such as MIL-53, where the large-pore (lp) form is intrinsically more stable than the narrow-pore (np) form at room temperature, our taxonomy predicts either the occurrence of two structural transitions upon gas adsorption or the absence of any transition.…”
mentioning
confidence: 99%
“…Many PICNICs exhibit hysteretic adsorption-desorption behavior which is often associated with the 'gate-opening' effect ( Figure 4). They also show dynamic host-guest behavior due to structural transitions which occur between the guest-free and guest-loaded states [78][79][80][81][82].…”
Section: Ni(cn) 4 -Based Mofs (Picnics)mentioning
confidence: 99%
“…Some MOFs can present structural flexibility or "breathing effects," which allows them to modulate their pore size upon adsorption of organic molecules into the pores, while their crystallinity is maintained [22,50,54,59]. One example of BioMOFs presenting a "breathing effect" is MIL-53 [22,54,100].…”
Section: Exploring the Potentialities Of The Breathing Effects On Biomentioning
confidence: 99%
“…Less toxic systems, using iron and more flexible MILs, are under study [25], and the first biodegradable therapeutic MOF, BioMIL-1, was reported by Miller et al in 2010 [27]. The large breathing effect that MOFs can attain is another particularly interesting feature for potential applications in drug delivery [54,59,52].…”
Section: Introductionmentioning
confidence: 99%